2012
DOI: 10.4236/ajps.2012.39145
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Influences Pre- and Post-Emergence Herbicide Efficacy in Corn

Abstract: Selecting a preemergence (PRE) and postemergence (POST) herbicide program that has the greatest efficacy can be difficult for corn producers and is highly dependent on weed spectrum. Weather conditions before and after herbicide application can further complicate decisions because they influence herbicide efficacy. Eleven field trials were conducted at three locations in Southwestern Ontario from 2003 to 2006, to determine the most effective PRE and POST corn herbicides for weed control. The most abundant weed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Weeds emerging after the 6th leaf stage of corn were small (low biomass/seedlings) and most likely did not reach reproductive maturity.In other studies, Stewart et al [8] found 91% -100% control of AMARE, 85% -100% of CHEAL and 78% -97% control of SETVI with a single POST application of glyphosate at 3 -4 leaf corn. Another study [20] found that ABUTH, AMARE, AM-BEL, CHEAL, and annual grasses were controlled 38% -93%, 93%, 99% -100%, 71% -100%, 30% -98% at 3 -4 leaf stage and 98% -99%, 100%, 78% -100%, 71% -98%, and 91% -100% at 7 -8 leaf stage in glyphosate resistant corn, respectively.…”
Section: Weed Biomass and Densitymentioning
confidence: 86%
See 1 more Smart Citation
“…Weeds emerging after the 6th leaf stage of corn were small (low biomass/seedlings) and most likely did not reach reproductive maturity.In other studies, Stewart et al [8] found 91% -100% control of AMARE, 85% -100% of CHEAL and 78% -97% control of SETVI with a single POST application of glyphosate at 3 -4 leaf corn. Another study [20] found that ABUTH, AMARE, AM-BEL, CHEAL, and annual grasses were controlled 38% -93%, 93%, 99% -100%, 71% -100%, 30% -98% at 3 -4 leaf stage and 98% -99%, 100%, 78% -100%, 71% -98%, and 91% -100% at 7 -8 leaf stage in glyphosate resistant corn, respectively.…”
Section: Weed Biomass and Densitymentioning
confidence: 86%
“…Glyphosate-resistant corn is popular in Eastern Canada as it provides many benefits to growers including excellent crop tolerance, a wide window of herbicide application, broad spectrum weed control, more consistent weed control under various environments, lower cost of weed control, greater yield, and higher net returns [5]. Growers often use one application of glyphosate applied early (EPOST) or late postemergence (LPOST) or a sequential application of glyphosate applied EPOST and LPOST as the primary weed management strategy to control troublesome weeds in glyphosate-resistant corn [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Selecting a preemergence (PRE) and postemergence (POST) herbicide program that has the greatest efficacy can be difficult for corn producers and is highly dependent on weed spectrum (Stewart et al, 2012). Management of weedsis considered to be an important factor for achieving higherproductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The exceptions to this were control of pigweed species using Clearout or WiseUp and control of green foxtail using WeatherMAX or WiseUp ( Table 1). In the literature, glyphosate has been highly efficacious (e.g., greater than 90% control) on these weed species found in maize, but across years and/or locations this level of control still may not be equivalent to a weed-free control [7] [15] [16]. At 4 WAT, WeatherMAX, Clearout, and WiseUp provided equivalent control of all weed species with two exceptions: WiseUp provided better control of common ragweed than Clearout at 450 g·ae·ha −1 and WiseUp provided better control of common lambsquarters than Clearout at 225 g·ae·ha −1 .…”
Section: Weed Control Using Low Glyphosate Dosesmentioning
confidence: 99%